A BIOGRAPHY OF THE LATE SENIOR CHIEF KATHURU NYAGAH OF THAGICU- KITUI COUNTY, KENYA,1918-1998 - Mugendi, Peter; Wafula, Peter; Nyambura, Ruth (IJRDO - Journal of Social Science and Humanities Research, 2022)
The study of biographies of those personalities who have contributed in one way or the other in influencing history can be quite fascinating because it furthers our understanding of broader issues and processes in any given society. Quite a number of historians have written biographies of those among the colonial chiefs who in one way or another played important roles in shaping the destinies of their people and of this country to a certain extent. There were those who utilized every opportunity created by the colonial officials to improve education, agriculture, health, water and infrastructure in their areas. Such colonial chiefs included senior chief Waruhiu wa Kung‟u, chief Musa Nyandusi, Odera Akong‟o, Njiri wa Karanja and paramount chief Kinyanjui Gathirimu just to name a few. As I read through the literature on colonial chiefs, it occurred to me that there is no one who has written a biography on colonial chiefs in Thagicu District even though there were a few chiefs among them the likes of senior chief Kathuru Nyagah and chief Mwendwa wa Kitavi who played very important roles in shaping the destinies of their people. The mention of the name of senior chief Kathuru among the Thagicu rekindles memories of a leader who through collaboration with colonial officials played a significant role in improving the lives of Thagicu people. Hence it is for this reason that this research was carried out with a view to exposing who chief Kathuru was and how and why he had become what he was. This thesis was an attempt to write the biography of the Late Senior Chief Kathuru Nyagah of Thagicu community.